Original Short Stories $1 (BVolume 05s - Maupassant, Guy de, 1850-1893; Henderson, A. E.; McMaster, Albert Cohn; Quesada, Louise Charlotte Garstin (Salt Lake City, UT : Project Gutenberg, 2004)
"Original Short Stories $1 (BVolume 05" by Guy de Maupassant is a collection of short stories written in the late 19th century, reflecting the intricacies of human relationships and social dynamics in a rapidly changing world. The initial story, "Monsieur Parent," introduces readers to the main character, Monsieur Parent, who navigates the turmoil of his familial life, grappling with infidelity and societal expectations in a tense domestic setting. The stories that follow promise a diverse exploration of themes such as love, betrayal, and existential reflection. At the start of "Monsieur Parent," we are immersed in the life of a man deeply devoted to his son, George, yet increasingly troubled by the emotional distance and infidelity of his wife. The scene unfolds in a park, where George plays innocently as his father reflects on their relationship and the looming presence of his wife's long absences. As the narrative progresses, the tension escalates with the revelation of his wife's affairs, particularly with a man named Limousin, prompting a devastating emotional confrontation for Parent. This opening portion skillfully sets the stage for a drama filled with jealousy, despair, and the longing for paternal connection, inviting readers to ponder the complexities of trust and family loyalty in Maupassant's nuanced storytelling. (This is an automatically generated summary.)s
Monsieur Parent -- Queen Hortense -- Timbuctoo -- Tombstones -- Mademoiselle Pearl -- The thief -- Clair de Lune -- Waiter, a "Bock" -- After -- Forgiveness -- In the spring -- A queer night in Paris.
Release date is 2004-10-03
Produced by David Widger
Keywords: Short stories, French -- Translations into English